(untitled) (Journal of Dhaka Medical College, 2010)
A prospective observational study was carried out in the Department of Plastic Surgery, Dhaka Medical College Hospital. 261 patients were included as study population that were referred from Casualty Surgery, Dhaka Medical College Hospital . This population represents 15.94% of the total trauma patients admitted in Casualty Department as emergency patient during the year 2009. Among them male patients were predominant (65.52%). On an average nearly 22 patients treated in a month as emergency patients. Most of the patients were between 30+-40 years and 20+-0 years age group. Aetiology of trauma according to history revealed road traffic accident as the cause in highest number of cases about 42.91% followed by machinery injury 34.86%. 41.76% of the injury managed in hand region which was highest. 34.87% of the patients were managed by flap cover and 49.42% patients required skin graft. Other various plastic surgical procedures were done in rest (15.71%) of the patients. Average hospital stay was 19.34±5.24 days among the admitted patients. Follow up of the patients showed that majority of the patients had full recovery (about 55.55%.) . DOI: 10.3329/jdmc.v18i2.6276 J Dhaka Med Coll. 2009; 18(2) : 144-149